2005
DOI: 10.1021/jo051654z
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Study of cis-1,4-Di-tert-butylcyclohexane by Dynamic NMR Spectroscopy and Computational Methods. Observation of Chair and Twist-Boat Conformations

Abstract: [reaction: see text] Low-temperature 13C NMR spectra of cis-1,4-di-tert-butylcyclohexane (1) showed signals for the twist-boat (1a) and chair (1b) conformations. 13C NMR signals were assigned to specific carbons based on the different populations, different symmetries (time-averaged C(2v) for 1a and time-averaged C(s) for 1b), and calculated chemical shifts (GIAO, HF/6-311+G*). In addition to slow ring inversion and interconversion of the chair and twist-boat conformations, slow rotation of the tert-butyl grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…The boat and envelope forms are transition states between the twist forms and the twist and chair forms respectively, and the twist-boat conformation is only 23 kJ/mol less stable than the chair conformation in solution [14]. In the current study, we found that most of the cyclohexanepolycarboxylate ligands adopt the chair forms in the organic adducts or coordination compounds in solid state.…”
Section: Introductionmentioning
confidence: 44%
See 1 more Smart Citation
“…The boat and envelope forms are transition states between the twist forms and the twist and chair forms respectively, and the twist-boat conformation is only 23 kJ/mol less stable than the chair conformation in solution [14]. In the current study, we found that most of the cyclohexanepolycarboxylate ligands adopt the chair forms in the organic adducts or coordination compounds in solid state.…”
Section: Introductionmentioning
confidence: 44%
“…The most interesting structural features for these three compounds is that a unique (H 2 O) 14 water cluster, which is the derivative of theoretically unstable (H 2 O) 12 cluster, and a truncated cubic (H 2 O) 12 cluster originated from coordinated and lattice water molecules were captured within the pores between two interpenetrating networks (Fig. 25).…”
Section: Coordination Compounds Based On 1245-cyclohexanetetracarbmentioning
confidence: 99%
“…Namely, the cyclohexane/benzene system seems to depart more from ideal mixing with increasing temperature, while the hexane/benzene one approaches to ideal mixing with increasing temperature. The deviation of V exc cyclo for cyclohexane/benzene system from the ideal mixing with increasing temperature would be due to the fact that cyclohexane exists in the two different forms (chair and boat formations) which are in equilibrium with each other: Although cyclohexane molecules exist mostly as chair formation at room temperature 16) , the increase in temperature may produce the increase in the ratio of boat-formed cyclohexane molecules. 3.1.3 Self-Diffusion Coefficients 3.1.3.1 Cyclohexane/benzene system presents the self-diffusion coefficients, D, of cyclohexane and benzene in the cyclohexane/benzene system at various temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The first step in the study involved the assignment of 1 H and 13 C NMR resonances of the molecule, and was accomplished in large part through interpretation of 1D spectra and analysis of COSY, HMQC, and HMBC experiments. As presented in Table 1, a number of characteristic correlations in the HMBC spectra could be readily attributed to the six-membered heterocycle (C-11/H-17 and C-17/H-11), the acetates (C-15/H-14, C-15/H-16, …”
Section: Resultsmentioning
confidence: 99%
“…Albeit consistent with the relative stereochemistry determined for the molecule, these NOEs position protons H-17 and H-13a in proximity to H-8 and as a result contradict the conformation proposed for the oxane ring. One possible interpretation of these observations involves the existence of multiple conformers that interconvert faster than the NMR time-scale, thus yielding a single set of 1 H and 13 C NMR signals and somewhat ambiguous NOE correlations. In order to assess this, variable-temperature experiments were performed between −50 and 50 • C. Except for a minor loss of resolution at low temperatures, no significant changes in the 1 H spectrum of 3 were observed in the range of temperatures studied (Fig.…”
Section: Resultsmentioning
confidence: 99%